Indicators of integration of Islamic values in human knowledge - Ismail, Nik Ahmad Hisham; Badrasawi, Kamal J I; Abu Kassim, Noor Lide (Springer Berlin Heidelberg, 2014)
The International Islamic University Malaysia (IIUM) is committed to the Integration of Islamic values in the Human Knowledge (IOHK), which is the core of its vision and mission. One of the main concerns of IOHK is to determine indicators to evaluate the implementation of IHOK at IIUM, and other Malaysian public institutions of higher learning. This study aims to explore the psychometric properties of a set of indicators measuring the integration of Islamic values in the curriculum at IIUM using the Rasch Measurement Model. This study utilized the survey method, with a 65-item questionnaire developed based on the literature review and data taken from focus group discussions. The items were divided into seven sub-constructs: Belief in IOHK (BI), Content of IOHK (CO), Teaching and Learning Process (TL), Evaluation (EV), Purpose of IOHK (PS), Product (PR), and Student Improvement (SI). A total of 324 academic staff randomly selected from various faculties at IIUM completed the questionnaire. The statistical software Winsteps, version 3.72.1 was used to conduct the analysis of the polytomous data collected. The Rasch analysis showed that overall item and person reliability values were very high (0.99 and 0.96 respectively), with item separation 10.51 and person separation 4.81. All items had positive point measure correlation coefficients, with few items below 0.3. Fit statistics estimates showed that all items were within the recommended acceptable range (0.5 -1.50), except 5 items on Belief in IOHK sub-construct. Variance explained by measures, indicated useful measurement (52.4%) with the variance explained by the first contrast in the residual less than 10%. The item and person means measures were well matched, 0.0 and 0.05 logit respectively. There were no gaps in the middle of the item distribution, but quite wide gaps were seen at the upper and lower ends of the scale. Some items were overlapping; however, they measure different aspects. The instrument as it stands provides useful measures. Nonetheless, the items related to belief of IOHK and Student Improvement, and the gaps at the opposite ends of the scale require qualitative investigation.